Source of Bleeding and Per-Operative Findings in Extradural Hematoma (Edh): A Three-Year Experience in Lady Reading Hospital Peshawar - Mansoor Ahmad; Naseer Hassan; Mehran Ali; Raza Hassan; Samir Khan Kabir (Gandhara University, 2022)
OBJECTIVES: The purpose of this study was to analyze the main source of bleeding and operative findings in an extradural hematoma (EDH).   METHODOLOGY: This study was conducted in the Department of Neurosurgery, Lady Reading Hospital, Peshawar. The sample size of the study was analyzed through WHO sample size calculator and 300 diagnosed patients were recruited by purposive sampling technique. Ethical approval was taken from the College of Physicians and Surgeons Pakistan (CPSP) and the hospital's ethical committee. By using the SPSS version 23.0, all the collected data were analyzed. RESULTS: The mean age of enrolled patients was 27.96±12.71 years. There were 65.7% male and 34.3% female. The most common age group was 21-30 years followed by 31 to 40 years and 11 to 20 years with the most common source of bleeding was middle meningeal artery, 39.7% of patients fall in the temporal parietal category. CONCLUSION: Middle meningeal artery is the most common source of bleeding in EDH. Therefore, proper management of this vessel is significant to avoid the chances of re-bleed and re-do surgeries.